Cytokines profile in pure neural leprosy - Pitta, Izabela Jardim R.; Angst, Debora Bartzen Moraes; Pinheiro, Roberta Olmo; Vieira, Joyce Soares da Silva; Spitz, Clarissa Neves; Andrade, Ligia Rocha; Carvalho, Larissa Bittencourt; Hacker, Mariana Andrea; Sarno, Euzenir Nunes; Jardim, Marcia Rodrigues (Frontiers in Immunology, 2023)
Introduction: Pure Neural Leprosy (PNL) is a form of this long time known disease that affects only the peripheral nervous system. Since it is a rare form of the disease, its pathophisiology is still poorly understood. Objective: Describe the cytokines profile in patients with PNL. Methods: 30 Patients diagnosed with PNL in the Souza Araujo Outpatient Clinic and with cytokines evaluated were selected. They were evaluated by neurologists and diagnosed after a nerve biopsy. Serum levels of IL-1 β, IL-6, IL-10, IL-17, TNF, CCL-2/MCP-1, IFN-ϒ, CXCL-10/IP-10 and TGF-β were evaluates at the moment of the diagnosis. Results: Neural thickening was a common clinical finding in this groups of patients. Small and medium sensitive fibers signs and symptoms were present in 92% of the patients and motor involvement in 53%. 43% of patients presented neuropathic pain and no one had neuritis TGF-beta, IL-17, CCl-2 and IP-10. CCL-2 levels were associated with demyelinating patters and IP-10 and IL-1o were associated with axonal patterns at NCS. Discussion: PNL patients’ cytokine profile appears to be different of other clinical forms of leprosy, with the presence of cytokines described in both tuberculoid and lepromatous leprosy. High levels of CCl-2 may be related to the presenc